Egalitarian Awareness in the Capitalistic Reality. The Entanglement of Poverty and Wealth in Daily Social Sphere 25 Years after the System Change in Poland - Żuk, Piotr (Studia Historiae Oeconomicae, 2014)
The purpose of the article is to illustrate the social order preferred by the Polish together with their assessment of the existing social inequalities. On the basis of the empirical material collected among the sample of 1000 respondents, the findings show manners of their definition of equity, perception of discrepancies between the ideal of equity and the existing real status, together with their assessment of the existing differences in the treatment of rich and poor people by various institutions (banks, police, hospitals, courts). The article also describes the causes of social inequalities as indicated by the respondents and their assessment of state policies in reference to them. The article concludes that 25 years after the collapse of “real socialism”, Polish society presents a firmly egalitarian awareness that is in conflict with the current market order.